2011
DOI: 10.1080/00981389.2011.588130
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience and the Fortunes of War

Abstract: Military families have been a subject of concern due to increasing divorce rates and child maltreatment that have been directly linked to the number and length of combat deployments. In contrast many military families show positive resilience in the wake of multiple deployments. This article looks at several special situations where military families are faced with serious challenges after deployment: soldiers returning with post-traumatic stress disorder, soldiers receiving serious injuries, and those killed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…Data on the impact of divorce in a military setting are especially important given the increasing rates of marital distress associated with the recent conflicts [10, 12, 14]. After controlling for baseline sociodemographics and health status, this study showed significant associations between divorce and new-onset PTSD, depression, smoking initiation and recidivism, alcohol-related problems, binge drinking, and moderate weight gain.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Data on the impact of divorce in a military setting are especially important given the increasing rates of marital distress associated with the recent conflicts [10, 12, 14]. After controlling for baseline sociodemographics and health status, this study showed significant associations between divorce and new-onset PTSD, depression, smoking initiation and recidivism, alcohol-related problems, binge drinking, and moderate weight gain.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies have demonstrated that infidelity and consideration of separation/divorce among military couples have increased during the recent conflicts [14, 15]. Further, service members returning from the war with PTSD or serious injuries, including traumatic brain injury, can strain the marital bond [12]. Overall, these data suggest the importance of exploring the potential effects of divorce on health and military outcomes among service members during an era of persistent conflicts, because these outcomes not only affect quality of life, but also military force readiness [16].…”
Section: Introductionmentioning
confidence: 99%
“…Many families do adjust-often with a reconfiguration of family responsibilities and duties, development of new routines, and a greater sense of self-confidence on the part of the at-home spouse when challenges are successfully met (Chapin, 2011). For other families, mental health of children or spouses may suffer during and after deployment.…”
mentioning
confidence: 94%
“…Surprisingly, using data from the personnel records of all U.S. service members in the last decade, Karney and Crown (2007) found that marital stability actually increased with greater overall time away, and was associated with a reduction of risk in marital dissolution. However, they did not include in their analysis couples that were married prior to 2001, suggesting that couples who married after 2001 may have been more prepared for multiple deployments than others, thus the higher rates of divorce reported elsewhere among military families (e.g., Chapin, 2011). While there obviously may be some variation in how families respond to greater cumulative lengths of deployment, in the present study, it was conceptualized as a contextual feature that would have an additive effect on the overall stress experienced by a family, likely impairing functioning.…”
Section: Literature Supporting the Proposed Modelmentioning
confidence: 99%